Assessment of triacylglycerol content in Chlorella vulgaris cultivated in a two-stage process. (September 2016) - dos Santos, Raquel Rezende; Kunigami, Claudete Norie; Gomes Aranda, Donato Alexandre; Luz Lapa Teixeira, Cláudia Maria
Abstract: Chlorella vulgaris cultivation in two-stage process was applied to increase the lipid productivity without compromising the biomass productivity. At the first stage, microalgae was cultivated under nutrient sufficient conditions to obtain a maximized cell density; at the second stage, nitrate conditions are changed to trigger the accumulation of TAG. During first stage, the maximum biomass productivity (32 mg L −1  d −1 ) was observed after 13 days under nutrient sufficient conditions with 1.21 g L −1  NaNO3 and 0.00449 g L −1  K2 HPO4 . Maximum lipid content (25.4% DW), lipid productivity (7.5 mg L −1  d −1 ) and TAG content (41.3% in total lipids) were favored by the nitrogen starvation conditions for more 4 days, at the second stage. Oil extracted at the second stage contained lower percentage of PUFAs being more suitable for the biodiesel production when compared with the oil extracted at the first stage. This two-stage phototrophic process is promising to provide a more efficient way for on a large-scale production of algal biomass and biodiesel production. Highlights: Nutrient-sufficient conditions favored the cell growth at the first stage. Nitrate-starvation conditions favored the lipid content at the second stage. Two-stage cultivation increased the TAG content without compromising the cell growth.